2014
DOI: 10.1371/journal.pone.0092020
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Contribution of CISH Promoter Polymorphisms to Susceptibility to Tuberculosis in Chinese Children

Abstract: Tuberculosis (TB) is the leading cause of death due to an infectious disease worldwide, particularly in developing countries. A series of candidate genes have been suggested to be associated with development of TB disease. Among them, the human Cytokine-inducible Src homology 2(SH2) domain protein (CISH) gene has been very recently reported to be involved in T cell activation and differentiation in response to Mycobacterium tuberculosis infection. Here, we studied the association between CISH promoter polymorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 33 publications
1
16
2
Order By: Relevance
“…Human genetic linkage studies of CISH have shown an association between CISH genetic variants and susceptibility to bacteremia, malaria, and tuberculosis (Khor et al 2010;Sun et al 2014), as well as persistent hepatitis B virus (HBV) infection or clearance of HBV (Tong et al 2012;Hu et al 2014;Song et al 2014). The molecular mechanism of CISH-related infection regulation remains to be clarified.…”
Section: Negative Regulation Of Cytokine Signaling In Immunitymentioning
confidence: 99%
“…Human genetic linkage studies of CISH have shown an association between CISH genetic variants and susceptibility to bacteremia, malaria, and tuberculosis (Khor et al 2010;Sun et al 2014), as well as persistent hepatitis B virus (HBV) infection or clearance of HBV (Tong et al 2012;Hu et al 2014;Song et al 2014). The molecular mechanism of CISH-related infection regulation remains to be clarified.…”
Section: Negative Regulation Of Cytokine Signaling In Immunitymentioning
confidence: 99%
“…Nonetheless, the activity of SOCS2 seems to be scarce and redundant and still requires a better understanding. CIS, on the other hand, is associated with increased susceptibility to TB (Sun et al, 2014 ; McCormick and Heller, 2015 ), likely by negatively regulating SOCS1 and SOCS3 (Trengove and Ward, 2013 ).…”
Section: Bacterial Pathogenesis and Immune Responsementioning
confidence: 99%
“…In line with these findings, knockdown in CIS impaired vaccine-induced responses, CTL development, and anti-tumor immunity ( 91 ). Human polymorphisms in the CIS promoter have been linked with increased susceptibility to ( 92 ) pediatric M. tuberculosis infection ( 93 ). Given the critical role of CIS in antigen presentation, cytokine production, and DC-mediated T cell priming, it is easy to appreciate how decreased CIS expression could interfere with vaccination efforts as well as predispose children to unchecked bacterial dissemination once contracting tuberculosis.…”
Section: Socs2 and Cis In Macrophage And Dendritic Cell Polarization mentioning
confidence: 99%